Does living at moderate altitudes in Austria affect mortality rates of various causes? An ecological study - Martin Burtscher; Johannes Burtscher; Gregoire P Millet (BMJ Open)
Objectives The effects of altitude residence on ageing, longevity and mortality are poorly understood. While adaptations to chronic exposure to altitude may exert beneficial effects on cardiovascular risk factors and some types of cancer, an elevated risk to die from chronic respiratory diseases has been reported. Moreover, high-altitude residence may be correlated with increased depression and suicide rates. The present study tested the hypothesis that living at moderate altitudes (up to 2000 m) is associated with reduced mortality from all causes.Setting and participants We used a dataset comprising all deaths (n=467 834) across 10 years of a country (Austria) characterised by varying levels of altitudes up to 2000 m.Main outcome measures Total number of deaths, age-standardised mortality rates (ASMRs) per 100 000 population, cause-specific ASMRs.Results ASMRs for residents living in higher (>1000 m) versus lower (<251 m) altitude regions (with agriculture employment below 3%) were 485.8 versus 597.0 (rate ratio and 95% CI 0.81 (0.72 to 0.92); p<0.001) for men and 284.6 versus 365.5 (0.78; 0.66 to 0.91); p=0.002) for women. Higher levels of agriculture employment did not influence mortality rates. Diseases of the circulatory system and cancers were main contributors to lower mortality rates at higher altitude. Residence at higher altitude did not negatively affect mortality rates from any other diseases. We highlight gender effects and—beside environmental factors—also discuss socioeconomic factors that may be responsible for conflicting results with data from other populations.Conclusions Living at moderate altitude (1000–2000 m) elicits beneficial effects on all-cause mortality for both sexes, primarily due to lower ASMRs from circulatory diseases and cancer. The presented analysis on cause-specific ASMRs over a 10-year period among the entire population of an alpine country will contribute to a better understanding on the effects of altitude-related mortality.